`y = e^p(p + psqrt(p))` Differentiate.

Textbook Question

Chapter 3, 3.2 - Problem 17 - Calculus: Early Transcendentals (7th Edition, James Stewart).
See all solutions for this textbook.

1 Answer | Add Yours

balajia's profile pic

balajia | College Teacher | (Level 1) eNoter

Posted on

`y(p)=e^p(p+p^(3/2))`

`y'(p)=e^p(p+p^(3/2))+e^p(1+(3/2)p^((3/2)-1))`

`y'(p)=e^p(p+p^(3/2)+1+(3/2)p^(1/2))`

`y'(p)=e^p(p+1+psqrtp+(3/2)sqrtp)`

``

We’ve answered 318,935 questions. We can answer yours, too.

Ask a question